2019
DOI: 10.1016/j.eurox.2019.100045
|View full text |Cite
|
Sign up to set email alerts
|

Does polycystic ovary syndrome affect morphokinetics or abnormalities in early embryonic development?

Abstract: Objectives This study aimed to investigate whether oocyte retrieval from PCOS patients affects the morphokinetics or the incidence of abnormalities in early embryonic development, using time-lapse imaging analysis. Methods This was a prospective study in total of 39 PCOS patients and 67 women with normal ovarian function, underwent a GnRH antagonist protocol of controlled ovarian stimulation and fertilization by ICSI. 402 zygotes from the PCOS group and 449 zygotes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…However, Nikbakht et al [ 6 ] did report the total stimulation doses that were used in the studied groups. Although the women of the PCOS-Anta group of our study and Le et al study [ 5 ] were stimulated with similar doses, women in the Control-Anta group of our study were stimulated with a little higher dosage of gonadotropins compared to those from Le et al study [ 5 ] and produced higher number of retrieved oocytes. Thus, the increase in stimulators dose did not arise from a lower response to gonadotropins.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…However, Nikbakht et al [ 6 ] did report the total stimulation doses that were used in the studied groups. Although the women of the PCOS-Anta group of our study and Le et al study [ 5 ] were stimulated with similar doses, women in the Control-Anta group of our study were stimulated with a little higher dosage of gonadotropins compared to those from Le et al study [ 5 ] and produced higher number of retrieved oocytes. Thus, the increase in stimulators dose did not arise from a lower response to gonadotropins.…”
Section: Discussionmentioning
confidence: 59%
“…On the other side, our results on the GnRH antagonist protocol were consistent with the results of the prospective study of Afiat et al [ 7 ], which could not detect any significant differences in the number of MII oocytes and MI oocytes between PCOS (n = 50) and controls (n = 50) that treated with GnRH antagonist protocol. Differently, the prospective study of Le et al [ 5 ] showed higher numbers of retrieved oocytes and mature oocytes in the PCOS group (n = 39) compared to the control one (n = 67) during the GnRH antagonist protocol. Similarly, the retrospective study of Nikbakht et al [ 6 ] also found a higher number of retrieved oocytes in the PCOS group.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations